The Palpable Legacy of Mid-Victorian Sensation Fiction: Sarah Waters’s Fingersmith (2002) and its Dialogue with Wilkie Collins’s The Woman in White (1860) - Catherine Delyfer (Cahiers Victoriens et Edouardiens)
This article first sketches out the legacy of The Woman in White and the sensation novel of the 1860s from the late-Victorian period to the present day. Then, in the second part of the essay, Sarah Waters’s novel Fingersmith (2002) is used as an exemplary text which illustrates some of the ways in which contemporary fiction has engaged with the Victorian sensation novel: after exploring Waters’s allusions to The Woman in White and discussing the politics of pastiche, as well as the concept of character ‘migration’, this article demonstrates that Waters’s appeal to the sense of touch borrows from Wilkie Collins’s tactile poetics, in order to invite us to read haptically, that is to say, to reconnect with a form of reading which is embodied and makes the Victorian past a palpable, substantial part of our contemporary selves.